PELAKSANAAN MODEL DISCOVERY LEARNING PADA PELATIHAN MENJAHIT DI LEMBAGA KURSUS DAN PELATIHAN (LKP) GITA PERTIWI TRAINING CENTRE TAMBUN SELATAN BEKASI - Tambunan, Grace Octaviani; Santika, Tika; Meilya, Ika Rizqi (IKIP Siliwangi, 2025)
This research is motivated by the high unemployment rate among the productive-age population, which necessitates improved work competencies through non-formal education, such as sewing training at a vocational training center (LKP). The study aims to describe the implementation of the Discovery Learning model in sewing training and to identify its supporting and inhibiting factorsat the LKP Gita Pertiwi Training Centre in South Tambun, Bekasi. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation with the center’s management, tutors, and students. Theresearch findings indicate that the implementation of Discovery Learning at this LKP follows six stages: stimulation, problem identification, data collection, data processing, verification, and generalization. Supporting factors include students’ cognitive readiness, learning motivation, and tutor facilitation. Inhibiting factors involve time constraints, limited critical thinking readiness, and inadequate learning facilities. Discovery Learning can foster independence and skills when supported by an effective learning system.